Analisis Dampak Negatif Terhadap Kebiasaan Mengunyah Sirih - Tiara Nanda Puspita Tanjung (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Indonesian people have been practicing the tradition of chewing betel continuously since the sixth century AD. People who carry out the tradition of betel nut are believed to strengthen teeth, remove bad odors from the body, and provide the same benefits as smoking tobacco. Periodontal disease which in fact can occur due to betel nut chewing (chewing). Since plaque is a major cause of periodontal disease, the two conditions are often used interchangeably. The periodontal ligament is a supporting structure for the gums. Gum tissue, periodontal ligament, adjacent alveolar bone, and cementum form the framework of the periodontal tissue. The gingiva is that part of the mandibular mucosa that covers the alveolar ridge and protects the underlying nerves and blood vessels. This research was conducted in the Tuntungan area, with a focus on the capital city of Medan. The research methodology consisted of a journal-based literature review and a qualitative survey. The results showed that of the 10 articles that raised the topic Habit of betel chewing on periodontal tissue damage. Based on the relevant analysis, it is known that more frequent betel chewing indicates a higher risk of periodontal damage.